2007
DOI: 10.1097/01.tp.0000255320.00061.e9
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factor-Induced Mobilization of Dendritic Cells in Kidney and Liver of Rhesus Macaques: Implications for Transplantation

Abstract: Hematopoietic growth factors (HGF) mobilize potential tolerogenic cells in transplant donors. Fms-like tyrosine kinase 3 ligand (Flt3L) mobilizes stem cells and dendritic cells (DCs) in human and nonhuman primate blood. Blood and renal and liver biopsies were obtained from untreated and Flt3L-mobilized rhesus macaques. Flt3L increased the number of myeloid CD11c(hi) and plasmacytoid CD123(hi) precursors in blood and both myeloid CD11c(+) HLA-DR(+) fascin(+) (CD45RA(-)) DCs and putative plasmacytoid CD11c(lo) C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Future studies will be needed to address these issues as well as to determine if findings in mice apply to humans, given the immunologic differences anticipated in scale up from mice to men, as recognized in hemophilia gene transfer [29]. The recent successful induction of transplant tolerance by immature DC in mouse transplant models, is currently being studied in larger animal models [30], including rhesus monkeys; and a clinical trial of immature DC, shown to be successful in the treatment of diabetes in mouse models has been initiated in patients with type 1 diabetes [31]. Hopefully, these preliminary studies of DC immunotherapy will provide preliminary insights into the application of this strategy in the prevention and suppression of anti-F.VIII antibodies in individuals with hemophilia.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies will be needed to address these issues as well as to determine if findings in mice apply to humans, given the immunologic differences anticipated in scale up from mice to men, as recognized in hemophilia gene transfer [29]. The recent successful induction of transplant tolerance by immature DC in mouse transplant models, is currently being studied in larger animal models [30], including rhesus monkeys; and a clinical trial of immature DC, shown to be successful in the treatment of diabetes in mouse models has been initiated in patients with type 1 diabetes [31]. Hopefully, these preliminary studies of DC immunotherapy will provide preliminary insights into the application of this strategy in the prevention and suppression of anti-F.VIII antibodies in individuals with hemophilia.…”
Section: Discussionmentioning
confidence: 99%
“…45 In human renal allografts and in IgA nephropathy, a very low number of DC-SIGN-positive cells were described in the glomeruli (1/50 and 1/12, respectively). 15 In contrast, Morelli et al 46 described an accumulation of DCs in the glomeruli and the tubulointerstitium in non-human primates after mobilization with Fmslike tyrosine kinase 3 ligand. Our results are applicable to only those antigens used here, particularly DC-SIGN, and we cannot rule out a DC-SIGN-negative population of intraglomerular DCs.…”
Section: Dc-sign Facilitates Interaction With Resting T Cells (Via Icmentioning
confidence: 95%
“…Systemic administration of Flt3L to mice55 and non-human primates56 has enabled expansion of both renal cDC and pDC in vivo . Ex vivo, freshly-isolated mobilized DC retain an immature phenotype and promote CD4 + CD25 + IL-10-producing regulatory T cells (Treg) 55.…”
Section: Renal DC and Mac In Homeostasismentioning
confidence: 99%